2015
DOI: 10.1039/c5ta04905a
|View full text |Cite
|
Sign up to set email alerts
|

Panchromatic polymer–polymer ternary solar cells enhanced by Förster resonance energy transfer and solvent vapor annealing

Abstract: Thanks to the bulk-heterojunction (BHJ) feature of polymer solar cells (PSC), additional light active components can be added with ease to form ternary solar cells. This strategy has achieved great success largely due to expanded spectral response range and improved power conversion efficiency (PCE) without incurring excessive processing costs. Here, we report ternary blend polymer-polymer solar cells comprised of PTB7, P3HT, and PC 71 BM with PCE as high as 8.2%.2 Analysis from femtosecond time resolved photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
44
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 70 publications
0
44
0
Order By: Relevance
“…[44] Thus nanowires and nanorods resulting in a 3D-N can be created using a top-down approach. TPF is one of the commonly used methods to make MGN-based one-body electrodes, where the formation of MGNs is controlled under the amorphous state above the glass transition temperature (T g ) during the solidification.…”
Section: Top-down Approachmentioning
confidence: 99%
“…[44] Thus nanowires and nanorods resulting in a 3D-N can be created using a top-down approach. TPF is one of the commonly used methods to make MGN-based one-body electrodes, where the formation of MGNs is controlled under the amorphous state above the glass transition temperature (T g ) during the solidification.…”
Section: Top-down Approachmentioning
confidence: 99%
“…Previous examples of controlling the morphology have been demonstrated including thermal annealing, solvent annealing, in‐situ annealing, solvent selection, post additive soaking, and solvent additives . Among them, the solvent additives approach has attracted significant attention as a convenient and time‐saving methodology .…”
Section: Introductionmentioning
confidence: 99%
“…8,9 These ternary blends exhibit charge transfer 5 or energy transfer. 6,10,11 It has been shown that the F€ orster Resonance Energy Transfer (FRET) effect on polymer-polymer poly [4,8- [3,4-b]thiophenediyl] (PTB7); poly [9-(1-octylnonyl)-9H-carbazole-2,7-diyl]-2,5-thiophenediyl-2,1,3-benzothiadiazole-4,7-diyl-2,5-thiophenediyl] (PCDTBT) and [6,6]-phenyl C 71 butyric acid methyl ester (PC 71 BM) ternary blend system boosts the efficiency of conventional BHJ-PSCs. 6 Further, dual donor and multidonor systems show improved PCE in excess of 9% due to energy transfer and efficient charge transport.…”
Section: à3mentioning
confidence: 99%